Using Dictogloss Procedure to Improve Students’ Recount Writing Skill - Meylina Meylina (LINGUA LITERA : journal of english linguistics and literature, 2016)
The purposes of this research were to explain whether dictogloss procedure can better improve students’ recount writing skill at grade X4of SMAN 1 Curup Timur of Bengkulu and explain what factors influence it through classroom action research. The research was done in 3 cycles.The findings of this research showed that the students’ recount writing skill improved after they implemented the dictogloss procedure. In cycle1 the mean score of students’ recount writing skill increased to 1.26 if it was compared with the pre-test that was 1.04. In cycle 2 the scoreincreased to 2.13, while in cycle 3 became 3.12. The increasing was influenced by several factors, such as the students’ motivation in writingrecount text, the level of the text used in the procedure, and the group work. Therefore, it can be concluded that using dictogloss procedure canbetter improve students’ recount writing skill well.